Traffic Light Timer Control Using Raspberry Pi - Philip, Armandio; Putri, Cheetah Savana; Arifanggi, Putra Maula (Pandawan, 2019)
As time goes by and the development of the times is very rapid increase in the number of vehicle volumes is increasing from year to year, coupled with automotive manufacturers who release their products at prices below the standard. This of course can increase the volume of congestion which is the main problem, very heavy traffic causes more time wasted and consumes fuel. The solution offered to overcome the congestion problem is a Timer Traffic Light control system, which is a traffic management system on each road segment used to reduce congestion in traffic lights that occur in big cities today. For the future, this is very much needed, given the increasing number of vehicles queuing at the traffic light. In this study a controller model of Timer Traffic Light was created based on image processing with the Background Subtraction method using the Raspberry Pi. The Background Subtraction method is used to process images containing objects that have been captured on the highway using a camera, the images obtained can classify the condition of the road with parameters of empty, medium, and solid conditions. The images obtained are then forwarded to the Timer Traffic Light controller system with the hardware and software used in this study.